Global burden of pneumoconiosis from 1990 to 2021: a comprehensive analysis of incidence, mortality, and socio-demographic inequalities in 204 countries and territories - Zhang, Shenyu; Xiong, Jun; Ruan, Xinyi; Ji, Chongyan; Lu, Hanxin (Frontiers in Public Health, 2025)
BackgroundPneumoconiosis, a group of occupational lung diseases caused by prolonged inhalation of mineral dust, remains a critical global health threat due to persistent workplace exposures in high-risk industries such as mining, construction, and artificial stone processing. These occupational hazards are exacerbated by inadequate dust control measures, insufficient use of personal protective equipment (PPE), and underreporting in low-and middle-income countries (LMICs). Emerging industries, including engineered stone fabrication, have introduced new risks, leading to accelerated silicosis among younger workers. Despite global efforts to improve occupational safety, socio-economic disparities, regulatory gaps, and public health crises such as the COVID-19 pandemic have further complicated disease management. This study analyzes trends in the global burden of pneumoconiosis from 1990 to 2021, providing evidence to inform post-pandemic strategies for occupational health equity and dust exposure mitigation.MethodsThe data for this study were sourced from the Global Burden of Disease (GBD) 2021 database, utilizing age-standardized incidence rates (ASIR), prevalence rates (ASPR), mortality rates (ASDR), and disability-adjusted life years (DALYs) as the primary assessment indicators. Dynamic changes in the burden of pneumoconiosis were analyzed by estimating the annual percentage changes (EAPCs). The correlation between the Socio-Demographic Index (SDI) and the burden of pneumoconiosis was examined using Pearson correlation tests. Additionally, we conducted decomposition and inequality analyses and Bayesian Age-Period-Cohort (BAPC) to assess trends and distribution related to the pneumoconiosis burden.ResultsThe global incidence of pneumoconiosis increased from 42,187.99 cases in 1990 to 62,866.45 cases in 2021, accompanied by a rise in mortality rates. Notably, the burden of pneumoconiosis remains disproportionately higher among men than women across nearly all regions. The highest incidence and mortality rates were recorded in the age group of 80 years and older, with a pronounced gender disparity, particularly in East Asia and High-income North America. These rates were generally elevated in low-income and lower-middle-income regions, where males exhibited significantly higher ASIR and ASDR compared to females. No correlation was found between the SDI values and the pneumoconiosis burden. Additionally, absolute inequality among SDI countries decreased from 1990 to 2021, whereas relative inequality demonstrated an upward trend during the same period.